A Randomized Controlled Field Trial on Behavioural Modification Intervention Amongst High School students for Cardiovascular Disease Prevention in Zahedan, Iran. - Khoshkhou, Fatemeh (2011)
Cardiovascular disease (CVD) is the leading cause of death globally. Risk factors for coronary artery disease begin in childhood. A randomized controlled field trial was conducted to develop, implement and evaluate the effectiveness of a school-based intervention on behavioural risk factors for cardiovascular diseases, amongst high school students in Zahedan, Iran. A multi-stage random sampling was used to select high schools in Zahedan city (namely, 4 control schools and 4 intervention schools). This study was carried out in two phases, namely Phase I: Focus Group Discussion (FGD) and Development of the Module and Phase II: Implementation and Evaluation of the Module. In the first phase, FGD was utilized to develop a suitable CVD behavioural intervention programme for high school students. A CVD risk factor intervention programme was then formed. In the second phase, the CVD intervention programme was implemented for the intervention group for a period of three months. The main CVD intervention programme consisted of six theoretical sessions, an intervention box, two fruit programmes, one outside the school programme, two sports matches between schools and a workshop. Finally, the effectiveness of the CVD intervention program was evaluated. A validated and reliable questionnaire was used to obtain the necessary information before and after 3 months of intervention. The semi-structured questionnaire used in this study comprises of three themes, which include socio-demographic factors, CVD knowledge and CVD risk factors including unhealthy diet, physical inactivity, smoking, blood pressure and obesity. The sample size for FGD and CVD intervention were 200 (students, parents, teachers and school canteen provider) and 1600 (students) respectively. Descriptive and multivariate statistics were used for analysing the data using SPSS version 17. A total of 1,389 eligible students (607 interventions and 782 controls) completed the three-month study. Post-test results showed that the mean of CVD and diet knowledge, consumption of healthy food, diet behaviour and physical activity significantly increased in the intervention group than the control group (p<0.05). On the contrary, the mean intake of unhealthy food decreased in the intervention group but, no significant difference was found between two groups (p=0.503).In addition, the number of smokers in the intervention group was found to have decreased by one compared to the control group whereby the number of smokers was increased by 4 persons (p=0.014). Moreover, the percentage of overweight students decreased in the intervention group compared to the control group (p=0.001). Furthermore, a significant reduction was observed in the percentage of stage-one and stage-two hypertensions in the intervention group compared to those of the control group (p=0.001). The effect of the CVD programme on the CVD knowledge was high (ES=0.673) and this was only moderate for taking healthy food, diet knowledge and behaviour, with effect size of 0.40, 0.42 and 0.42, respectively, in the intervention group. The results of Mixed ANOVA model showed that gender has more affected the responses to the CVD intervention programs compared to the age, family income, mother and father education. In conclusion, CVD knowledge and particularly diet knowledge improved in the intervention group, and as a behaviour change, consumption of healthy foods increased in the intervention group significantly even after the three months short intervention. In addition, consumption of unhealthy foods, junk food and soft drink decreased in the intervention group. Adding of salt also decreased in the intervention group, and this change could be expected to improve the risk of hypertension in the future. Furthermore, it could be stipulated that this programme might be effective to be used in preventing students from initiating to smoke, becoming obese, and being in stages 1 and 2 of hypertensions. Finally, I support that this trial for CVD prevention by school-based approach is quite useful as a preliminary study and also would be expanded to big and long-term project in Iran in future.